REGULASI EMOSI GURU KELAS DALAM MENANGANI ANAK BERKEBUTUHAN KHUSUS : REGULASI EMOSI GURU KELAS DALAM MENANGANI ANAK BERKEBUTUHAN KHUSUS - alivia, betrik; Hasanah, uswatun (Universitas Darul Ulum, 2023)
This study aims to understand the emotional regulation of classroom teachers in dealing with children with special needs at SLB Nurul Ikhsan Ngadiluwih, Kediri Regency. The focus of this research is to find out how the classroom teacher's emotional regulation deals with children with special needs at SLB Nurul Ikhsan Ngadiluwih, Kediri Regency, the factors that influence the emotional regulation of class teachers in handling children with special needs at SLB Nurul Ikhsan Ngadiluwih, Kediri Regency. This study used a qualitative method with data collection techniques through in-depth interviews with class teachers at SLB Nurul Ikhsan Ngadiluwih. The data were analyzed thematically by identifying common patterns of emotion regulation used by classroom teachers and the factors that influence those processes. The results of the study show that classroom teacher emotional regulation plays an important role in dealing with children with special needs at SLB Nurul Ikhsan Ngadiluwih. Teachers use a variety of strategies, such as self-regulation, social support, relaxation techniques, and creating stable routines, to help students self-regulate their emotions. Factors that affect the classroom teacher's emotional regulation include education and training, work experience, support and collaboration, physical and social environment, and availability of resources. Teachers who have good knowledge and skills in emotion regulation can create an inclusive, positive, and supportive learning environment for children with special needs.